1992
DOI: 10.1002/cbf.290100203
|View full text |Cite
|
Sign up to set email alerts
|

Generation of hydrogen peroxide in resting and activated platelets

Abstract: The production of hydrogen peroxide was measured by following the oxidation of dichlorofluorescein (DCFH) entrapped into platelets. Resting platelets produced nanomolar quantities of DCF, which was proportional to the concentration of platelets and was steady during 1 h of incubation. A significant increase of basal DCF fluorescence was induced by stimuli namely thrombin, arachidonic acid, the Ca2+ ionophore A23187 and PMA. The effect of agonists has been also measured in the presence of 3-amino-1,2,4-triazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 27 publications
0
34
0
1
Order By: Relevance
“…Thus, treatment of female rats with estradiol reduced protein content, enzyme activity, and messenger RNA of GRK 2 in the hypothalamus (Ansonoff and Etgen, 2001). On the other hand, the platelet aggregation (induced by epinephrine) and reactivity are increased in depressed patients (García-Sevilla et al, 1986, 1990Musselman et al, 1996Musselman et al, , 2000, and activated platelets produce reactive oxygen species, such as hydrogen peroxide (Maresca et al, 1992) that can modulate the expression of GRKs. Thus, the exposure of lymphocytes to hydrogen peroxide resulted in marked decreases in GRK 2 expression and in agonistinduced desensitization of b 2 -adrenoceptors (Lombardi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treatment of female rats with estradiol reduced protein content, enzyme activity, and messenger RNA of GRK 2 in the hypothalamus (Ansonoff and Etgen, 2001). On the other hand, the platelet aggregation (induced by epinephrine) and reactivity are increased in depressed patients (García-Sevilla et al, 1986, 1990Musselman et al, 1996Musselman et al, , 2000, and activated platelets produce reactive oxygen species, such as hydrogen peroxide (Maresca et al, 1992) that can modulate the expression of GRKs. Thus, the exposure of lymphocytes to hydrogen peroxide resulted in marked decreases in GRK 2 expression and in agonistinduced desensitization of b 2 -adrenoceptors (Lombardi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In those studies it was also shown that NO, hydroxyl radical (OH × ) and metal ions do not oxidize 2,7-dichlorofluorescin. Some earlier reports have suggested that hydrogen peroxide also oxidized 2,7-dichlorofluorescin [12]. To test this, we incubated DCFDA (5 mmol/l) with either 100 mmol/l H 2 O 2 or 100 mmol/l ONOO ± for 15 min in PBS at 37°C.…”
Section: Methodsmentioning
confidence: 97%
“…The effect of increasing or lowering cellular GSH levels on kinamycin F-induced DNA strand breaks was also determined. In these parallel experiments K562 cells were pre-incubated with either OTC (5 mM ) or BSO (100 μM) for either 24 …”
Section: Fast Micromethods Dna Single-strand-break Assaymentioning
confidence: 99%